Are demographics associated with mucoepidermoid or acinic cell carcinoma parotid malignancies in children? - Tyler A. Janz (KeAi Communications Co., Ltd., 2019)
Objective: To identify possible associations between patient demographics and parotid cancer histological type in pediatric patients. Methods: Pediatric patients (ages: birth-18.0 years) in the Surveillance, Epidemiology, and End Results (SEER) database were included from 1973 to 2014 based on a diagnosis of mucoepidermoid carcinoma or acinic cell carcinoma of the parotid gland using the ICD O-3 codes of C07.9 and 8430 or 8550. Patients were classified into the following cohorts: <14 and 14–18 years of age based on the mean age at diagnosis. Results: Three hundred and three pediatric patients were diagnosed with mucoepidermoid carcinoma or acinic cell carcinoma of the parotid gland within the SEER 18 registries. Female pediatric patients 14–18 years of age were 7.68 times more likely to have an acinic cell carcinoma (adjusted OR: 7.68 [95% CI: 2.01–29.44]). When stratified by histological type, 58.9% of female pediatric patients ≥14 years of age had an acinic cell carcinoma as compared to 37.3% of male pediatric patients ≥14 years of age, 36.5% of female pediatric patients <14 years of age, and 34.0% of male pediatric patients <14 years of age (P = 0.01). Conclusions: Based on this study, pediatric female patients between the ages of 14 and 18 years are the most likely cohort to have acinic cell carcinoma. The results of this study may assist providers during the work up of a pediatric patient with a suspected parotid malignancy. Keywords: Pediatric parotid cancer, Head and neck surgery, Pediatric otolaryngology, Level of evidence: 4